Designing intersectional online education critical teaching and learning practices - Woodley, Xeturah M.; Rice, Mary 1980- (Routledge, Taylor & Francis Group, 2022)
Designing Intersectional Online Education provides expansive yet accessible examples and discussion about the intentional creation of online teaching and learning experiences that critically center identity, social systems, and other important ideas in design and pedagogy. Instructors are increasingly tasked with designing their own online courses, curricula, and activities but lack information to support their attention to the ever-shifting, overlapping contexts and constructs that inform students' positions within knowledge and schooling. This book infuses today's technology-enhanced education environments with practices derived from critical race theory, culturally responsive pedagogy, disability studies, feminist/womanist studies, queer theory, and other essential foundations for humanized and socially just education. Faculty, scholars, technologists, and other experts across higher education, K-12, and teacher training offer fresh, robust insights into how actively engaging with intersectionality can inspire designs for online teaching and learning that are inclusive, intergenerational, anti-oppressive, and emancipatory"--